Sensing the Synagogue - Stern, Karen B. (The Biblical archaeology review, 2026)
Synagogues became vital centers of Jewish religious and community life after the destruction of the Temple in 70 CE. Written and archaeological sources provide vivid testimony of how these structures were built, decorated, and sustained across the Mediterranean world of late antiquity. What was it like to worship inside these spaces? Explore how early Jews experienced the sights and smells of ancient synagogues.